2015
DOI: 10.1007/s00034-015-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Solutions of Quadrature Oscillators With Linear Control of Frequency of Oscillation Employing Modern Commercially Available Devices

Abstract: This paper proposes two circuits of frequency-controlled oscillators, whose structures are based only on simple commercially available active elements with minimum number of terminals, in particular, the differential voltage buffer, controllable B Roman Sotner Circuits Syst Signal Process voltage amplifier and electronically controllable current conveyor. Two methods for achieving linear control (tuning) of frequency of oscillations (FO) are discussed. The first method employs a simple structure. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…This problem can be solved by using automatic gain control (AGC) circuit. There are oscillators with AGC available in literature [58][59][60][61]. These techniques use AGC circuit including into the loop of the system for controlling the amplitude of signal.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem can be solved by using automatic gain control (AGC) circuit. There are oscillators with AGC available in literature [58][59][60][61]. These techniques use AGC circuit including into the loop of the system for controlling the amplitude of signal.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…14 was used. This circuit was adopted from [61]. From our pretest on the proposed circuit, it was found that V 1 (I 1 and I 3 ) was dependent on tuning of FO, thus V 1 will be used for the input of AGC circuit (V in(AGC) ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed floating inductance simulator shown in Fig. 1 employs three electronically adjustable current conveyors of second generation (ECCIIs) [16] described by the following inter-terminal transfers: IZ = B.IX, VX = VY, IY = 0 and one differential voltage buffer (DVB) [16] providing the following operation: V+  V = Vout. Note that the current gain B of each ECCII is controllable linearly by DC voltage (B  VSET_B).…”
Section: Description Of Floating Inductance Simulatormentioning
confidence: 99%
“…The synthesis of an analog circuit using commercially available ICs have been continuously proposed [16][17][18][19][20]. Especially the designs of voltage or current controlled quadrature sinusoidal oscillators using commercially available ICs have been found in the open literature [21][22][23][24][25][26][27][28][29][30][31]. Moreover, the linear voltage controlled sinusoidal oscillator using commercially available ICs-based CCII was proposed in [32].…”
Section: Introductionmentioning
confidence: 99%